2022
DOI: 10.1097/mnm.0000000000001645
|View full text |Cite
|
Sign up to set email alerts
|

The combined tumor-nodal glycolytic entropy improves survival stratification in nonsmall cell lung cancer with locoregional disease

Abstract: Objective To investigate whether combining primary tumor and metastatic nodal glycolytic heterogeneity on 18 F-fluorodeoxyglucose PET ( 18 F-FDG PET) improves prognostic prediction in nonsmall cell lung cancer (NSCLC) with locoregional disease. MethodsWe retrospectively analyzed 18 F-FDG PETderived features from 94 patients who had undergone curative treatments for regional nodal metastatic NSCLC. Overall survival (OS) and progression-free survival (PFS) were analyzed using univariate and multivariate Cox regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
1
0
0
Order By: Relevance
“…Our preliminary survival analysis also showed that a higher TMB, SUV max and entropy were associated with an unfavorable OS. Our results are compatible with the literature, where TMB and 18 F-FDG PET-derived features were found to be predictive of survival outcomes in patients with lung cancer [ 5 , 29 , 30 ]. However, the follow-up period of our cohort was short and the patient characteristics were heterogeneous.…”
Section: Discussionsupporting
confidence: 92%
“…Our preliminary survival analysis also showed that a higher TMB, SUV max and entropy were associated with an unfavorable OS. Our results are compatible with the literature, where TMB and 18 F-FDG PET-derived features were found to be predictive of survival outcomes in patients with lung cancer [ 5 , 29 , 30 ]. However, the follow-up period of our cohort was short and the patient characteristics were heterogeneous.…”
Section: Discussionsupporting
confidence: 92%